Cancers in the urban environment - Mack, Thomas M. (Academic Press, 2021)
Cancers in the Urban Environment: How Malignant Diseases Are Caused and Distributed among the Diverse People and Neighborhoods of a Major Global Metropolis, Second Edition, provides a detailed description of the occurrence of common forms of cancer in the ethnically, socially and environmentally complex milieu of a modern urban complex. The location is Los Angeles County, and the patterns of 72 different malignancies are described according to race, age, sex, social class calendar time (since 1972) and most notably, individual neighborhood, using detailed maps of high risk. This second edition uses twice as many cases and more demographic diversity. Physicians and scientific investigators in California and elsewhere can use the material provided to counsel patients and evaluate the consistency of any specific pattern of occurrence with each specific causal hypothesis. A detailed appendix describes the source of data, provides the basis for the choices made in the production of the volume, and gives a perspective on the search for "clusters" of malignancy.